Unlocking Potential Initiatives for Retracing the Public Service Delivery in a Uganda’s Case Amongst the African Countries - Kyohairwe, S. B. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
In spite of the fact that the public sector does not choose its customers, it is still necessary that the publics and their diverse needs should remain a priority factor, driving the need for new service and improved delivery models. The common belief amongst the beneficiaries of public services is that the traditional mandate of executing social policy and legislation enforcement remains a passive achievement without attempts to deliver on the customer promise. Amidst all the traditional and emerging governance and administrative challenges, the publics relentlessly remain hopeful for an improved customer experience and performance outcomes that respond to their needs through enhanced service levels within the current budgetary constraints. This paper therefore sets to assess perceived reasons for the current minimal levels of public service delivery as a foundation for identifying suitable the mechanisms for improved service delivery in Uganda. For a manageable study scope considering the fact that the public sector is too wide a subject area public opinions on the performance of different sectors are initially established and follow-up findings on the selected least performance rated sectors are explored. Suggestions for improvement are derived from the views of the service delivery assessments made.
Journal article published in The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Customer promise; Public sector reforms; Public service delivery; Post-New Public Management; Whole-of-Government; Public administration; Customer satisfaction